Dampak Program Sanggah Bersinar di Loka Rehabilitasi BNN Deli Serdang bagi Pemulihan Klien Pasca Rehabilitasi - Judika Adelin Sidabutar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to determine the impact of the Sanggah Sinar program on the recovery of post-rehabilitation clients who have been returned home. Post-rehabilitation clients and even post-rehabilitation client families often experience confusion in maintaining and helping clients maintain their recovery. Real recovery is not when the client is in rehabilitation, but when the client has returned home, and will continue his new life after undergoing the rehabilitation process. This rehabilitation or recovery aims to create a new life for clients, which includes three things, namely: 1) death life or how post-rehabilitation care 2) Hope & Optimism about the future 3) Empowerment. This research technique is a qualitative research methodology that collects data by conducting interviews, observations and documentation. processing data by analyzing data. In maintaining the recovery of clients who have returned home, several actions need to be taken, require care and need to pay attention to several things. Reorientation towards a recovered life is: 1) breaking ties with the drug circle 2) improving relationships with the social environment and people 3) making oneself more productive in everyday life 4) finding valuable values ​​as motivation to recover. 5) creating new coping (strategies) 6) family as the main foundation in recovery 7) building a new identity. The Sanggah Cemerlang program as a program carried out after rehabilitation or post-rehabilitation, has a fairly good impact on post-rehabilitation clients. In accordance with the BNN guidelines on the implementation of post-rehabilitation programs, the Sanggah Cemerlang program is good. and in pastoral counseling services, to deal with the diverse Indonesian society, dealing with post-rehabilitation clients by carrying out an innovative understanding of the spiritual dimension in the paradigm of Christian psychology and religion.